Mental health among adolescents exposed to social inequality in Latin America and the Caribbean: a scoping review - Sánchez-Castro, Johanna Carolina; Pilz González, Laura; Arias-Murcia, Saidy Eliana; Mahecha-Bermeo, Viviana Andrea; Stock, Christiane; Heinrichs, Katherina (Frontiers in Public Health, 2024)
Background and objective: Adolescents from Latin America and the Caribbean grow up in a context of social inequality, which diminishes their well-being and leads to impaired emotional-cognitive development. To understand the problem, it is important to synthesise the available research about it. This study aims to explore the knowledge about adolescents’ mental health in Latin America and the Caribbean exposed to social inequality. Methods: A systematic scoping review was conducted encompassing a search in five databases (Medline, CINAHL, PsycINFO, Scopus, and LILACS) in June 2022. Articles of various typologies were included without time limit. After two rounds of screening, relevant data were manually extracted and synthesised into self-constructed themes using thematic analysis. Results: Out of 8,825 retrieved records, 42 papers were included in the final review, with a predominance of quantitative approaches. The synthesis revealed two main analytical themes: a) defining social inequality, wherein intersecting inequalities produce discrimination and determine conditions for social vulnerability; b) social inequality and mental health, which highlights the association between socio-structural difficulties and emotional problems, amplifying vulnerability to mental ill health and poor mental health care. Conclusion: The scientific evidence reveals that social inequality is related to impaired well-being and mental ill health on the one hand and a lack of access to mental health care on the other hand.